Ion-conductive solid and all-solid-state battery
By adopting the oxide-based ion-conducting solid of the general formula Li6+a-c-2dX1-a-b-c-dM1aM2bM3cM4dB3O9, using low-temperature heat treatment and metal element replacement of different valences, the high resistance phase problem caused by high-temperature heat treatment in the prior art is solved, and the high resistance phase problem caused by high-temperature heat treatment in the prior art is realized. High ion conductivity and improved output performance of all solid-state batteries.
Patent Information
- Application Number
- CN202380051815.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-08
- Filing Date
- 2023-04-11
- Publication Date
- 2025-02-18
AI Technical Summary
The existing oxide-based solid electrolytes are prone to react with electrode active substances during high-temperature heat treatment to form high-resistance phases, resulting in a decrease in ion conductivity and a decrease in output of all-solid-state batteries.
The oxide-based ion-conducting solid of the general formula Li6+a-c-2dX1-a-b-c-dM1aM2bM3cM4dB3O9 is prepared by low-temperature heat treatment, and the charge balance is adjusted by displacement of metal elements of different valences to improve ion conductivity.
High ion conductive solid prepared by low-temperature heat treatment is achieved, the formation of high resistance phase is avoided, and the ionic conductivity and output performance of all-solid-state batteries are improved.
Smart Images

Figure BDA0005227711310000491 
Figure BDA0005227711310000511 
Figure BDA0005227711310000521
Abstract
Description
Technical Field
[0001] The present disclosure relates to ion-conducting solids and all-solid-state batteries. Background Art
[0002] Lightweight and high-capacity lithium-ion secondary batteries have long been used in mobile devices such as smartphones and laptops, as well as in transportation equipment such as electric vehicles and hybrid vehicles.
[0003] However, since conventional lithium-ion secondary batteries use liquids containing flammable solvents as electrolytes, there are concerns about leakage of the flammable solvents and fires when the batteries are short-circuited. Therefore, in recent years, in order to ensure safety, attention has been paid to secondary batteries that use ion-conductive solids as electrolytes, which are different from liquid electrolytes. Such secondary batteries are called all-solid-state batteries.
[0004] Solid electrolytes such as oxide-based solid electrolytes and sulfide-based solid electrolytes are widely known as electrolytes for all-solid-state batteries. Among them, oxide-based solid electrolytes do not react with moisture in the atmosphere to produce hydrogen sulfide, and are safer than sulfide-based solid electrolytes.
[0005] In addition, the all-solid-state battery has: a positive electrode containing a positive electrode active material; a negative electrode containing a negative electrode active material; an electrolyte containing an ion-conductive solid disposed between the positive electrode and the negative electrode; and a current collector as required (the positive electrode active material and the negative electrode active material are also collectively referred to as "electrode active material"). In the case of using an oxide-based solid electrolyte to prepare an all-solid-state battery, heat treatment is performed to reduce the contact resistance between particles of the oxide-based material contained in the solid electrolyte. However, since the previous oxide-based solid electrolytes require a high temperature of more than 900°C during heat treatment, the solid electrolyte and the electrode active material may react to form a high resistance phase. This high resistance phase may be related to a decrease in the ionic conductivity of the ion-conductive solid, and even to a decrease in the output of the all-solid-state battery.
[0006] Examples of oxide-based solid electrolytes that can be prepared by heat treatment at a temperature lower than 900° C. include Li 2+x C 1-x B x O3 (Non-Patent Document 1).
[0007] In addition, it is also disclosed that by comparing with the above-mentioned Li 2+x C 1-x B x O3 can improve properties by containing specific elements at a specific ratio (Patent Document 1).
[0008] Prior art literature
[0009] Non-patent literature
[0010] Non-patent document 1: Solid State Ionics, Vol. 288 (2016), pp. 248-252
[0011] Non-patent document 2: Acta Crystallographica Section A, Vol. 32 (1976), p. 751 (Acta Crystallographica Section A 32 (1976) 751)
[0012] Patent Literature
[0013] Patent Document 1: Japanese Patent No. 6948676 Summary of the invention
[0014] Problems to be solved by the invention
[0015] The present invention provides an ion conductive solid having high ion conductivity and which can be prepared by heat treatment at low temperature, and an all-solid-state battery having the ion conductive solid.
[0016] Technical solutions to solve problems
[0017] The ion-conductive solid of the present disclosure is characterized by containing a general formula Li 6+a-c-2d X 1-a-b-c- d M1 a M2 b M3 c M4 d Oxide represented by B3O9.
[0018] (wherein, X is at least one metal element selected from the group consisting of Lu, Ho, Er and Tm,
[0019] M1 is at least one metal element selected from the group consisting of Mg, Mn, Zn, Ni, Ca, Sr and Ba,
[0020] M2 is at least one metal element selected from the group consisting of La, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Lu, In, Fe and Sc,
[0021] M3 is at least one metal element selected from the group consisting of Zr, Ce, Hf, Sn and Ti,
[0022] M4 is at least one metal element selected from the group consisting of Nb and Ta,
[0023] a is a real number satisfying 0.000≤a≤0.800, b is a real number satisfying 0.000≤b≤0.900, c is a real number satisfying 0.000≤c≤0.800, d is a real number satisfying 0.000≤d≤0.800, and a, b, c, d are real numbers satisfying 0.000≤a+b+c+d<1.000. Except for the case where X and M2 are the same metal element.)
[0024] In addition, the all-solid-state battery disclosed in the present invention has at least a positive electrode, a negative electrode and an electrolyte, and is characterized in that:
[0025] At least one selected from the group consisting of the positive electrode, the negative electrode, and the electrolyte contains the ion-conductive solid of the present disclosure.
[0026] Effects of the Invention
[0027] According to one embodiment of the present disclosure, it is possible to obtain an ion conductive solid having high ion conductivity and which can be prepared by heat treatment at a low temperature, and an all-solid-state battery having the ion conductive solid. DETAILED DESCRIPTION
[0028] In the present disclosure, unless otherwise specified, the description of "XX or more and YY or less" and "XX to YY" indicating a numerical range refers to a numerical range including the lower limit and the upper limit of the endpoints. When the numerical range is described in stages, the upper and lower limits of each numerical range can be arbitrarily combined.
[0029] Furthermore, in the present disclosure, “solid” refers to a substance having a certain shape and volume among the three states of matter, and a powder state is included in the “solid”.
[0030] The ion-conducting solid disclosed herein is a solid having a general formula Li 6+a-c-2d X 1-a-b-c-d M1 a M2 b M3 C M4 d An ion-conductive solid of an oxide represented by B3O9.
[0031] In the formula, X is at least one metal element selected from the group consisting of Lu, Ho, Er and Tm,
[0032] M1 is at least one metal element selected from the group consisting of Mg, Mn, Zn, Ni, Ca, Sr and Ba,
[0033] M2 is at least one metal element selected from the group consisting of La, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Lu, In, Fe and Sc,
[0034] M3 is at least one metal element selected from the group consisting of Zr, Ce, Hf, Sn and Ti,
[0035] M4 is at least one metal element selected from the group consisting of Nb and Ta,
[0036] a is a real number satisfying 0.000≤a≤0.800, b is a real number satisfying 0.000≤b≤0.900, c is a real number satisfying 0.000≤c≤0.800, d is a real number satisfying 0.000≤d≤0.800, and a, b, c, d are real numbers satisfying 0.000≤a+b+c+d<1.000, except when X and M2 are the same metal element.
[0037] Except for the case where X and M2 are the same metal element,
[0038] When X is Lu, M2 is at least one metal element selected from the group consisting of La, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, In, Fe and Sc,
[0039] When X is Ho, M2 is at least one metal element selected from the group consisting of La, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Er, Tm, Lu, In, Fe and Sc,
[0040] When X is Er, M2 is at least one metal element selected from the group consisting of La, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Tm, Lu, In, Fe and Sc,
[0041] When X is Tm, M2 is at least one metal element selected from the group consisting of La, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Lu, In, Fe and Sc.
[0043] The present inventors presume the following as the reason why the ion conductivity of the ion conductive solid containing the oxide represented by the above general formula is improved.
[0044] By replacing Y in Li6YB3O9 in Comparative Example 1 in Patent Document 1 with at least one metal element selected from the group consisting of Lu, Ho, Er and Tm having a smaller ionic radius than Y, the lattice constant and lattice volume are reduced. + It becomes easier to move, so the ionic conductivity increases.
[0045] On the other hand, in Patent Document 1, a part of Y, which is a trivalent metal element, is substituted with a tetravalent to pentavalent metal element, that is, elements with different valences are substituted to adjust the charge balance and improve the ion conductivity.
[0046] By using a metal element with an appropriate ionic radius as the metal element X instead of Y, the lattice constant and lattice volume are reduced. + It becomes easier to move, so the ion conductivity is further improved. In addition, it is also a preferred method to use elements of different valences in combination.
[0047] The ionic radius of X is preferably More preferably More preferably Particularly preferred By falling within the above range, the lattice constant and the lattice volume become small. As a result, Li + becomes easy to move, so the ionic conductivity increases. In addition, when the ionic radius is smaller than , the target monoclinic structure cannot be obtained and thus it will not become an ion conductive solid.
[0048] The value of the ionic radius can be the value described in Non-Patent Document 2. For example, Y 3+ The ionic radius is Lu 3 + The ionic radius is Ho 3+ The ionic radius is Er 3+ The ionic radius is Tm 3+ The ionic radius is
[0049] The ion-conductive solid of the present disclosure preferably has a monoclinic crystal structure.
[0050] The volume average particle size of the ion conductive solid disclosed in the present invention is preferably 0.1 μm to 28.0 μm, more preferably 0.2 μm to 26.0 μm, further preferably 0.3 μm to 20.0 μm, further preferably 0.3 μm to 15.0 μm, and further preferably 0.5 μm to 10.0 μm. Within the above range, the grain boundary resistance in the ion conductive solid is reduced and the ion conductivity is further improved.
[0051] The volume average particle size of the ion conductive solid can be controlled by pulverization or classification.
[0052] In the above general formula, a is a real number satisfying 0.000≤a≤0.800.
[0053] a is 0.000≤a≤0.800, preferably 0.000≤a≤0.600, more preferably 0.000≤a≤0.400, further preferably 0.000≤a≤0.100, particularly preferably 0.000≤a≤0.050, and very preferably 0.000≤a≤0.030.
[0054] In the above general formula, b is a real number satisfying 0.000≤b≤0.900.
[0055] b is 0.000≤b≤0.900, preferably 0.000≤b≤0.600, more preferably 0.000≤b≤0.500, further preferably 0.000≤b≤0.400, further preferably 0.000≤b≤0.100, particularly preferably 0.000≤b≤0.050, and very preferably 0.000≤b≤0.030.
[0056] In the above general formula, c is a real number satisfying 0.000≤c≤0.800.
[0057] c is 0.000≤c≤0.800, preferably 0.000≤c≤0.600, more preferably 0.000≤c≤0.400, further preferably 0.000≤c≤0.150, further preferably 0.000≤c≤0.100, particularly preferably 0.000≤c≤0.050, and very preferably 0.000≤c≤0.030. In addition, the following method can be adopted, that is, c is preferably 0.050≤c≤0.200, and more preferably 0.080≤c≤0.150.
[0058] In the above general formula, d is a real number satisfying 0.000≤d≤0.800.
[0059] d is 0.000≤d≤0.800, preferably 0.000≤d≤0.600, more preferably 0.000≤d≤0.400, further preferably 0.000≤d≤0.100, particularly preferably 0.000≤d≤0.050, and very preferably 0.010≤d≤0.030.
[0060] In the above formula, a+b+c+d is a real number satisfying 0.000≤a+b+c+d<1.000.
[0061] a+b+c+d is 0.000≤a+b+c+d<1.000, preferably 0.000≤a+b+c+d<0.900, more preferably 0.000≤a+b+c+d<0.800, further preferably 0.000≤a+b+c+d<0.700, further preferably 0.000≤a+b+c+d≤0.600, particularly preferably 0.010≤a+b+c+d<0.500, especially preferably 0.050≤a+b+c+d<0.300, and very preferably 0.080≤a+b+c+d<0.250.
[0062] X 1-a-b-c-d 1-abcd in is preferably 0.300≤1-abcd, more preferably 0.500≤1-abcd, further preferably 0.700≤1-abcd, and further preferably 0.750≤1-abcd. Although the upper limit is not particularly limited, it is preferably less than 1.000, less than 0.950, and less than 0.900. For example, the range of preferably 0.300≤1-abcd<1.000, 0.500≤1-abcd≤0.950, and 0.700≤1-abcd≤0.900 can be cited.
[0063] The ion conductive solid of the present disclosure can adopt the following embodiments, for example, but is not limited to these embodiments. (1)
[0065] a satisfies 0.010≤a≤0.100, b satisfies 0.000≤b≤0.200, c satisfies 0.000≤c≤0.200, d satisfies 0.010≤d≤0.100, and a, b, c, d satisfy 0.010≤a+b+c+d<0.300. (2)
[0067] a satisfies 0.010≤a≤0.030, b satisfies 0.030≤b≤0.100, c satisfies 0.010≤c≤0.030, d satisfies 0.010≤d≤0.030, and a, b, c, d satisfy 0.050≤a+b+c+d<0.160. (3)
[0069] a satisfies 0.000≤a≤0.010, b satisfies 0.000≤b≤0.100, c satisfies 0.050≤c≤0.150, d satisfies 0.000≤d≤0.030, and a, b, c, d satisfy 0.050≤a+b+c+d<0.250.
[0070] Regarding M1, M2, M3, and M4 in the above general formula, they may be included in the formula or not. That is, at least one of a, b, c, and d may be 0.
[0071] In the above general formula, M1 is at least one metal element selected from the group consisting of Mg, Mn, Zn, Ni, Ca, Sr and Ba.
[0072] M1 is at least one selected from the group consisting of Mg, Mn, Zn, Ni, Ca, Sr and Ba, preferably at least one selected from the group consisting of Mg, Zn, Ca, Sr and Ba, and more preferably at least one selected from the group consisting of Mg, Ca and Sr.
[0073] In the above general formula, M2 is at least one metal element selected from the group consisting of La, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Lu, In, Fe and Sc.
[0074] M2 is at least one selected from the group consisting of La, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Lu, In, Fe and Sc, preferably at least one selected from the group consisting of La, Eu, Gd, Tb, Dy, Lu, In and Fe, and more preferably at least one selected from the group consisting of Gd, Dy, Lu, In and Fe. In addition, M2 may be at least one selected from the group consisting of La, Pr, Nd, Sm, Eu, Gd, Tb, Dy, In, Fe and Sc.
[0075] In the above general formula, M3 is at least one metal element selected from the group consisting of Zr, Ce, Hf, Sn and Ti.
[0076] M3 is at least one selected from the group consisting of Zr, Ce, Hf, Sn and Ti, preferably at least one selected from the group consisting of Zr, Ce, Hf and Sn, and more preferably at least one selected from the group consisting of Zr, Ce and Hf.
[0077] In the above general formula, M4 is at least one metal element selected from the group consisting of Nb and Ta.
[0078] M4 is at least one selected from the group consisting of Nb and Ta, and is preferably Nb.
[0079] Furthermore, when a part of X, which is a trivalent metal element, is replaced with specific elements M1, M2, M3, and M4 within a specific ratio range, the charge balance can be adjusted by replacing elements with different valence numbers. + In a defective state. Due to the surrounding Li+ Will move to fill the Li + defects, thus increasing the ionic conductivity.
[0080] Next, the method for producing the ion conductive solid of the present disclosure will be described.
[0081] The method for producing the ion conductive solid of the present disclosure may be as follows, but is not limited thereto.
[0082] A compound having the general formula Li 6+a-c-2d X 1-a-b-c-d M1 a M2 b M3 c M4 d A method for producing an ion-conductive solid of an oxide represented by B3O9, wherein
[0083] There may be a primary calcination step in which raw materials mixed to obtain the oxide represented by the general formula are heat-treated at a temperature lower than the melting point of the oxide.
[0084] In the formula, X is at least one metal element selected from the group consisting of Lu, Ho, Er and Tm,
[0085] M1 is at least one metal element selected from the group consisting of Mg, Mn, Zn, Ni, Ca, Sr and Ba,
[0086] M2 is at least one metal element selected from the group consisting of La, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Lu, In, Fe and Sc,
[0087] M3 is at least one metal element selected from the group consisting of Zr, Ce, Hf, Sn and Ti,
[0088] M4 is at least one metal element selected from the group consisting of Nb and Ta,
[0089] a is a real number satisfying 0.000≤a≤0.800, b is a real number satisfying 0.000≤b≤0.900, c is a real number satisfying 0.000≤c≤0.800, d is a real number satisfying 0.000≤d≤0.800, and a, b, c, d are real numbers satisfying 0.000≤a+b+c+d<1.000, except when X and M2 are the same metal element.
[0090] The method for producing an ion conductive solid disclosed herein may include a primary firing step: weighing and mixing raw materials to obtain an oxide represented by the above general formula, and heat treating the raw materials at a temperature lower than the melting point of the oxide to prepare an ion conductive solid containing the oxide. The ion conductive solid can be obtained by the primary firing step.
[0091] Furthermore, the production method may further include a secondary calcination step, if necessary, of heat-treating the obtained ion conductive solid containing an oxide at a temperature lower than the melting point of the oxide to prepare a sintered body of the ion conductive solid containing the oxide.
[0092] Hereinafter, the method for producing the ion conductive solid of the present disclosure including the primary calcination step and the secondary calcination step will be described in detail, but the present disclosure is not limited to the following production method.
[0093] One-shot firing process
[0094] In the primary calcination process, chemical reagent grade raw materials such as Li2CO3, H3BO3, HO2O3, ZrO2, CeO2, HfO2 are weighed in stoichiometric amounts and mixed to form a general formula Li 6+a-c-2d X 1-a-b-c-d M1 a M2 b M3 c M4 d B3O9 (wherein X is at least one metal element selected from the group consisting of Lu, Ho, Er and Tm,
[0095] M1 is at least one metal element selected from the group consisting of Mg, Mn, Zn, Ni, Ca, Sr and Ba,
[0096] M2 is at least one metal element selected from the group consisting of La, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Lu, In, Fe and Sc,
[0097] M3 is at least one metal element selected from the group consisting of Zr, Ce, Hf, Sn and Ti,
[0098] M4 is at least one metal element selected from the group consisting of Nb and Ta,
[0099] a is a real number satisfying 0.000≤a≤0.800, b is a real number satisfying 0.000≤b≤0.900, c is a real number satisfying 0.000≤c≤0.800, d is a real number satisfying 0.000≤d≤0.800, and a, b, c, d are real numbers satisfying 0.000≤a+b+c+d<1.000. Except for the case where X and M2 are the same metal element).
[0100] The device for mixing is not particularly limited, but for example, a pulverizing mixer such as a planetary ball mill can be used. The material and capacity of the container used during mixing and the material and diameter of the ball are not particularly limited, and can be appropriately selected according to the type and usage of the raw materials used. As an example, a 45mL container made of zirconium oxide and a 5mm diameter ball made of zirconium oxide can be used. In addition, the conditions of the mixed treatment are not particularly limited, but for example, a rotating speed of 50rpm to 2000rpm and a time of 10 minutes to 60 minutes.
[0101] After the mixed powder of the raw materials is obtained by the mixing process, the obtained mixed powder is subjected to pressure molding to form particles. As the pressure molding method, a known pressure molding method such as cold unidirectional molding method and cold water pressure molding method can be used. The pressure molding conditions in the primary sintering process are not particularly limited, and for example, the pressure can be 100MPa to 200MPa.
[0102] The obtained particles are fired using a firing device such as an atmospheric firing device. The temperature of the solid phase synthesis is lower than the temperature of the general formula Li 6+a-c-2d X 1-a-b-c-d M1 a M2 b M3 c M4 d The melting point of the ion conductive solid represented by B3O9 is not particularly limited. The temperature during the primary calcination may be, for example, less than 700°C, less than 680°C, less than 670°C, less than 660°C or less than 650°C, for example, more than 500°C. This numerical range may be combined arbitrarily. As long as the temperature is within the above range, solid phase synthesis can be fully performed. The time of the primary calcination process is not particularly limited, but may be, for example, about 700 minutes to 750 minutes.
[0103] Through the above-mentioned primary calcination step, a molten metal containing the above-mentioned general formula Li 6+a-c-2d X 1-a-b-c- d M1 a M2 b M3 c M4 dAn ion-conductive solid of an oxide represented by B3O9. The ion-conductive solid containing the oxide can also be obtained as a powder by pulverizing the ion-conductive solid containing the oxide using a mortar and pestle or a planetary mill.
[0104] Secondary firing process
[0105] In the secondary calcination step, at least one selected from the group consisting of the ion conductive solid containing oxide and powder of the ion conductive solid containing oxide obtained in the primary calcination step is pressure-molded and calcined as necessary to obtain a sintered body of the ion conductive solid containing oxide.
[0106] Pressure forming and secondary sintering can be performed simultaneously using spark plasma sintering (hereinafter also referred to as "SPS"), hot pressing, etc., or after preparing particles by cold unidirectional forming, secondary sintering can be performed in an air atmosphere, an oxidizing atmosphere, or a reducing atmosphere. As long as the above conditions are met, an ion conductive solid with high ion conductivity can be obtained without causing melting due to heat treatment. There are no particular restrictions on the conditions for pressure forming in the secondary sintering process, and for example, the pressure can be 10MPa to 100MPa.
[0107] The temperature of the secondary sintering is lower than that of the general formula Li 6+a-c-2d X 1-a-b-c-d M1 a M2 b M3 c M4 d The melting point of the ion conductive solid represented by B3O9. The temperature during the secondary calcination is preferably less than 700°C, more preferably less than 680°C, further preferably less than 670°C, and particularly preferably less than 660°C. The lower limit of the temperature is not particularly limited, and the lower the better, but for example it is above 500°C. This numerical range can be combined arbitrarily, but for example it can be in the range of 500°C to less than 700°C. As long as it is within the above range, the melting or decomposition of the ion conductive solid containing the oxide disclosed in the secondary calcination process can be suppressed, and a fully sintered sintered body of the ion conductive solid containing the oxide disclosed in the present invention can be obtained.
[0108] The time of the secondary firing step can be appropriately changed according to the temperature and pressure of the secondary firing, but is preferably 24 hours or less, and may be 14 hours or less. The time of the secondary firing step may be, for example, 5 minutes or more, 1 hour or more, or 6 hours or more.
[0109] The method for cooling the sintered body of the ion conductive solid containing the oxide of the present disclosure obtained by the secondary calcination step is not particularly limited, and it may be cooled naturally (furnace cooling), rapidly cooled, gradually cooled rather than cooled naturally, or maintained at a certain temperature during cooling.
[0110] Next, the all-solid-state battery of the present disclosure will be described.
[0111] An all-solid-state battery generally includes a positive electrode, a negative electrode, an electrolyte containing an ion-conductive solid and disposed between the positive electrode and the negative electrode, and a current collector as needed.
[0112] The all-solid-state battery disclosed herein is an all-solid-state battery having at least a positive electrode, a negative electrode, and an electrolyte, wherein at least one selected from the group consisting of the positive electrode, the negative electrode, and the electrolyte contains the ion-conductive solid disclosed herein.
[0113] The all-solid-state battery disclosed in the present invention may be a bulk type battery or a thin film type battery. The specific shape of the all-solid-state battery disclosed in the present invention is not particularly limited, but examples thereof include coin type, button type, sheet type, stacked type, and the like.
[0114] The all-solid-state battery of the present disclosure has an electrolyte. In addition, in the all-solid-state battery of the present disclosure, it is preferred that at least the electrolyte contains the ion-conductive solid of the present disclosure.
[0115] The solid electrolyte in the all-solid-state battery of the present disclosure may be composed of the ion conductive solid of the present disclosure, may contain other ion conductive solids, and may contain ionic liquids and gel polymers. Other ion conductive solids are not particularly limited, and may contain ion conductive solids commonly used in all-solid-state batteries, such as LiI, Li3PO4, Li7La3Zr2O 12 The content of the ion conductive solid of the present disclosure in the electrolyte of the all-solid-state battery of the present disclosure is not particularly limited, but is preferably 25% by mass or more, more preferably 50% by mass or more, further preferably 75% by mass or more, and particularly preferably 100% by mass.
[0116] The all-solid-state battery disclosed in the present invention has a positive electrode. The positive electrode may contain a positive electrode active material, or may contain the positive electrode active material and the ion conductive solid disclosed in the present invention. As the positive electrode active material, a known positive electrode active material such as a sulfide containing a transition metal element, an oxide containing lithium and a transition metal element, etc. may be used without particular limitation. For example, LiNiVO4, LiCoPO4, LiCoVO4, LiMn 1.6 Ni 0.4O4, LiMn2O4, LiCoO2, Fe2(SO4)3, LiFePO4, LiNi 1 / 3 Mn 1 / 3 CO 1 / 3 O2、LiNi 1 / 2 Mn 1 / 2 O2, LiNiO2, Li 1+x (Fe, Mn, Co) 1-x O2、LiNi 0.8 CO 0.15 Al 0.05 O2, etc.
[0117] Furthermore, the positive electrode may also contain a binder, a conductive agent, etc. Examples of the binder include polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl alcohol, etc. Examples of the conductive agent include natural graphite, artificial graphite, acetylene black, ethylene black, etc.
[0118] The all-solid-state battery disclosed in the present invention has a negative electrode. The negative electrode may contain a negative electrode active material, or may contain the negative electrode active material and the ion conductive solid disclosed in the present invention. As the negative electrode active material, lithium, lithium alloys, inorganic compounds such as tin compounds, carbonaceous materials capable of absorbing and releasing lithium ions, conductive polymers, and other known negative electrode active materials may be used without particular limitation. For example, Li4Ti5O 12 wait.
[0119] Furthermore, the negative electrode may further contain a binder, a conductive agent, etc. As the binder and the conductive agent, the same materials as those exemplified for the positive electrode can be used.
[0120] Here, the electrode "containing" an electrode active material means that the electrode has the electrode active material as a component, element, and property. For example, whether the electrode active material is contained in the electrode or the electrode active material is coated on the surface of the electrode, it is equivalent to the above-mentioned "containing".
[0121] The positive electrode and the negative electrode can be obtained by known methods such as mixing raw materials, molding, and heat treatment. Therefore, it can be considered that the ion conductive solid enters the gap between the electrode active materials, etc., making it easy to ensure the conduction path of lithium ions. It can be considered that the ion conductive solid disclosed in the present invention can be prepared by low-temperature heat treatment compared with the prior art, so that the formation of a high resistance phase generated by the reaction of the ion conductive solid with the electrode active material can be suppressed.
[0122] The positive electrode and the negative electrode may also have a current collector. As the current collector, a known current collector such as aluminum, titanium, stainless steel, nickel, iron, calcined carbon, conductive polymer, conductive glass, etc. may be used. In addition, in order to improve adhesion, conductivity, oxidation resistance, etc., a material obtained by treating the surface of aluminum, copper, etc. with carbon, nickel, titanium, silver, etc. may also be used as the current collector.
[0123] The all-solid-state battery disclosed in the present invention can be obtained, for example, by stacking, molding, and heat treating the positive electrode, solid electrolyte, and negative electrode in a known manner. Since the ion-conductive solid disclosed in the present invention can be prepared by low-temperature heat treatment compared to the prior art, it can be considered that the formation of a high-resistance phase generated by the reaction of the ion-conductive solid with the electrode active material can be suppressed, and an all-solid-state battery with excellent output characteristics can be obtained.
[0124] Next, the composition and the measurement methods of various physical properties involved in the present disclosure are described.
[0125] Identification and analysis methods of metal content
[0126] The composition analysis of the ion conductive solid is performed by wavelength dispersive X-ray fluorescence analysis (hereinafter also referred to as XRF) using a sample solidified by pressure molding. However, in the case where analysis is difficult due to particle size effects, the ion conductive solid can be vitrified by the glass bead method to perform composition analysis based on XRF. In addition, in the case where the yttrium peak overlaps with the metal-containing peak in XRF, composition analysis can be performed by inductively coupled plasma atomic emission spectrometry (ICP-AES).
[0127] In the case of XRF, the analysis device used was a ZSX Primus II manufactured by Rigaku Corporation. The analysis conditions were as follows: Rh was used as the anode of the X-ray tube, the analysis diameter was 10 mm, the analysis range was 17 to 81 degrees, the step length was 0.01 degrees, and the scanning speed was 5 seconds / step. In addition, a proportional counter was used for the measurement of light elements, and a scintillation counter was used for the measurement of heavy elements.
[0128] The elements were identified based on the peak positions of the spectrum obtained by XRF, and the molar concentration ratio was calculated from the number of X-ray photons per unit time, that is, the count rate (unit: cps), to determine a, b, c, and d.
[0129] Example
[0130] Hereinafter, examples of specifically preparing and evaluating the ion conductive solid of the present disclosure will be described as examples. In addition, the present disclosure is not limited to the following examples.
[0131] [Example 1]
[0132] ·One-shot firing process
[0133] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass%), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Lu2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass%), and Nb2O5 (manufactured by Mitsui Mining and Smelting, purity 99.9%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that d became the value recorded in Table 1, and mixed for 30 minutes at a disk speed of 300 rpm using a planetary mill P-7 manufactured by Fritsch. The planetary mill used was made of zirconium oxide. Ball and 45mL container.
[0134] After mixing, the mixed powder was cold uniaxially molded at 147 MPa using a 100 kN electric press device P3052-10 manufactured by NPASYSTEM, and then sintered in an air atmosphere at a heating temperature of 650° C. and a holding time of 720 minutes.
[0135] The obtained oxide-containing ion-conductive solid was pulverized for 180 minutes using a planetary mill P-7 manufactured by Fritsch Co., Ltd. at a disk rotation speed of 230 rpm to prepare a powder of the oxide-containing ion-conductive solid.
[0136] Secondary firing process
[0137] The powder of the ion conductive solid containing oxide obtained in the above manner was molded and secondary fired to prepare a sintered body of the ion conductive solid containing oxide of Example 1. The molding was performed by cold unidirectional molding of the powder at 147 MPa using a 100 kN electric press device P3052-10 manufactured by NPASYSTEM. The secondary firing was performed in an air atmosphere at a heating temperature of 650° C. and a holding time of 720 minutes.
[0138] [Example 2]
[0139] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Lu2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass %) and CeO2 (manufactured by Shin-Etsu Chemical Co., Ltd., purity 99.9%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that c became the value recorded in Table 1. Except for this, the sintered body of the ion conductive solid containing oxide of Example 2 was prepared by the same process as Example 1.
[0140] [Example 3]
[0141] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Lu2O3 (manufactured by Kojun Chemical Laboratory, purity 99.9 mass %), ZrO2 (manufactured by Nippon Denko, purity 99.9%), CeO2 (manufactured by Shin-Etsu Chemical, purity 99.9%) and Nb2O5 (manufactured by Mitsui Mining and Smelting, purity 99.9%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that c and d became the values recorded in Table 1. Except for this, the sintered body of the oxide-containing ion conductive solid of Example 3 was prepared by the same process as Example 1.
[0142] [Example 4]
[0143] A sintered body of an ion conductive solid containing an oxide of Example 4 was prepared by the same steps as in Example 1, except that the raw materials used in the above Examples were weighed in stoichiometric amounts so as to obtain the values shown in Table 1.
[0144] [Example 5]
[0145] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Lu2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass %) and HfO2 (manufactured by New Metals, purity 99.9%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that c became the value recorded in Table 1. Except for this, a sintered body of an ion-conductive solid containing oxide of Example 5 was prepared by the same process as Example 1.
[0146] [Example 6]
[0147] A sintered body of an ion conductive solid containing an oxide of Example 6 was prepared by the same steps as in Example 1, except that the raw materials used in the above Examples were weighed in stoichiometric amounts so that c would have the value shown in Table 1.
[0148] [Example 7]
[0149] A sintered body of an ion conductive solid containing an oxide of Example 7 was prepared by the same steps as in Example 1, except that the raw materials used in the above Examples were weighed in stoichiometric amounts so that c and d would have the values shown in Table 1.
[0150] [Example 8]
[0151] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Lu2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass %), In2O3 (manufactured by Shinko Chemical Industry, purity 99 mass %), SnO2 (manufactured by Mitsuwa Chemicals, purity 99.9%) and CeO2 (manufactured by Shin-Etsu Chemical Co., Ltd., purity 99.9%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that b and c became the values recorded in Table 1. Except for this, the sintered body of the oxide-containing ion conductive solid of Example 8 was prepared by the same process as Example 1.
[0152] [Example 9]
[0153] A sintered body of an ion conductive solid containing an oxide of Example 9 was prepared by the same steps as in Example 1, except that the raw materials used in the above Examples were weighed in stoichiometric amounts so that b and c would have the values shown in Table 1.
[0154] [Example 10]
[0155] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Lu2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass %), Fe2O3 (manufactured by Wako Pure Chemical Industries, purity 95.0 mass %) and TiO2 (manufactured by TOHO TITANIUM, purity 99%) were used as raw materials, and each raw material was weighed in a stoichiometric amount in such a way that b and c became the values recorded in Table 1. Except for this, the sintered body of the ion conductive solid containing oxide of Example 10 was prepared by the same process as Example 1.
[0156] [Example 11]
[0157] A sintered body of an ion conductive solid containing an oxide of Example 11 was prepared by the same steps as in Example 1, except that the raw materials used in the above Examples were weighed in stoichiometric amounts so that b and c would have the values shown in Table 1.
[0158] [Example 12]
[0159] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass%), B2O3 (manufactured by Wako Pure Chemical Industries, Ltd., purity 99.9 mass%), Ho2O3 (manufactured by High Junction Chemical Research Institute, purity 99.9 mass%) and Lu2O3 (manufactured by High Junction Chemical Research Institute, purity 99.9 mass%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that b became the value recorded in Table 1. Except for this, a sintered body of an ion conductive solid containing oxide of Example 12 was prepared by the same process as Example 1.
[0160] [Example 13]
[0161] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Lu2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass %), MgO (manufactured by Ube Materials, purity 99.0 mass %) and CeO2 (manufactured by Shin-Etsu Chemical Co., Ltd., purity 99.9%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and c became the values shown in Table 1. Except for this, the sintered body of the oxide-containing ion conductive solid of Example 13 was prepared by the same process as Example 1.
[0162] [Example 14]
[0163] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass%), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Lu2O3 (manufactured by Kojun Chemical Laboratories, purity 99.9 mass%), La2O3 (manufactured by Wako Pure Chemical Industries, purity 99.9 mass%), MgO (manufactured by Ube Materials, purity 99.0 mass%) and CaO (manufactured by Kanto Chemical, purity 97.0 mass%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and b became the values shown in Table 1. Except for this, the sintered body of the oxide-containing ion conductive solid of Example 14 was prepared by the same process as Example 1.
[0164] [Example 15]
[0165] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Lu2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass %), La2O3 (manufactured by Wako Pure Chemical Industries, Ltd., purity 99.9 mass %) and MnO (manufactured by Kanto Chemical, purity 80.0 mass %) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and b became the values shown in Table 1. Except for this, the sintered body of the ion conductive solid containing oxide of Example 15 was prepared by the same process as Example 1.
[0166] [Example 16]
[0167] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Lu2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass %), Tb2O3 (manufactured by Shin-Etsu Chemical Co., Ltd., purity 99.9 mass %) and MnO (manufactured by Kanto Chemical, purity 80.0 mass %) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and b became the values recorded in Table 1. Except for this, the sintered body of the oxide-containing ion conductive solid of Example 16 was prepared by the same process as Example 1.
[0168] [Example 17]
[0169] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Lu2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass %), Tm2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass %) and MnO (manufactured by Kanto Chemical, purity 80.0 mass %) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and b became the values shown in Table 1. Except for this, the sintered body of the ion conductive solid containing oxide of Example 17 was prepared by the same process as Example 1.
[0170] [Example 18]
[0171] A sintered body of an ion conductive solid containing an oxide of Example 18 was prepared by the same steps as in Example 1, except that the raw materials used in the above Examples were weighed in stoichiometric amounts so that c and d would have the values shown in Table 1.
[0172] [Example 19]
[0173] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass%), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Lu2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass%), In2O3 (manufactured by Shinko Chemical Industry, purity 99 mass%), Nb2O5 (manufactured by Mitsui Mining and Smelting, purity 99.9%) and Ta2O5 (manufactured by Kanto Chemical, purity 99 mass%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that b and d became the values recorded in Table 1. Except for this, the sintered body of the oxide-containing ion conductive solid of Example 19 was prepared by the same process as Example 1.
[0174] [Example 20]
[0175] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Lu2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass %) and Pr2O3 (manufactured by Shin-Etsu Chemical Co., Ltd., purity 99.9 mass %) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that b became the value recorded in Table 1. Except for this, a sintered body of an ion-conductive solid containing oxide of Example 20 was prepared by the same process as Example 1.
[0176] [Example 21]
[0177] A sintered body of an ion conductive solid containing an oxide of Example 21 was prepared by the same steps as in Example 1, except that the raw materials used in the above Examples were weighed in stoichiometric amounts so that b and d would have the values shown in Table 1.
[0178] [Example 22]
[0179] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass%), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Lu2O3 (manufactured by Kojun Chemical Laboratories, purity 99.9 mass%), Sm2O3 (manufactured by Wako Pure Chemical Industries, Ltd., purity 99.9 mass%), HfO2 (manufactured by New Metals, purity 99.9%) and Ta2O5 (manufactured by Kanto Chemical, purity 99 mass%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that b, c and d became the values recorded in Table 1. Except for this, the sintered body of the oxide-containing ion conductive solid of Example 22 was prepared by the same process as Example 1.
[0180] [Example 23]
[0181] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass%), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Lu2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass%), Nd2O3 (manufactured by Shin-Etsu Chemical, purity 99.9 mass%), Sm2O3 (manufactured by Wako Pure Chemical Industries, Ltd., purity 99.9 mass%) and ZnO (manufactured by Wako Pure Chemical Industries, Ltd., purity 99 mass%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and b became the values shown in Table 1. Except for this, the sintered body of the oxide-containing ion conductive solid of Example 23 was prepared by the same process as Example 1.
[0182] [Example 24]
[0183] A sintered body of an ion conductive solid containing an oxide of Example 24 was prepared by the same steps as in Example 1, except that the raw materials used in the above Examples were weighed in stoichiometric amounts so that b and c would have the values shown in Table 1.
[0184] [Example 25]
[0185] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Lu2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass %) and Eu2O3 (manufactured by Shin-Etsu Chemical Co., Ltd., purity 95 mass %) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that b became the value recorded in Table 1. Except for this, a sintered body of an ion-conductive solid containing oxide of Example 25 was prepared by the same process as Example 1.
[0186] [Example 26]
[0187] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass%), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Lu2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass%), Eu2O3 (manufactured by Shin-Etsu Chemical Co., Ltd., purity 95 mass%) and NiO (manufactured by Wako Pure Chemical Industries, Ltd., purity 99.0 mass%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and b became the values shown in Table 1. Except for this, the sintered body of the ion conductive solid containing oxide of Example 26 was prepared by the same process as Example 1.
[0188] [Example 27]
[0189] A sintered body of an ion conductive solid containing an oxide of Example 27 was prepared by the same steps as in Example 1, except that the raw materials used in the above Examples were weighed in stoichiometric amounts so that b and c would have the values shown in Table 1.
[0190] [Example 28]
[0191] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass%), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Lu2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass%), Gd2O3 (manufactured by Shin-Etsu Chemical, purity 99.9 mass%), Dy2O3 (manufactured by Shin-Etsu Chemical, purity 95 mass%) and CaO (manufactured by Kanto Chemical, purity 99.0 mass%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and b became the values shown in Table 1. Except for this, the sintered body of the oxide-containing ion conductive solid of Example 28 was prepared by the same process as Example 1.
[0192] [Example 29]
[0193] A sintered body of an ion conductive solid containing an oxide of Example 29 was prepared by the same steps as in Example 1, except that the raw materials used in the above Examples were weighed in stoichiometric amounts so that b and c would have the values shown in Table 1.
[0194] [Example 30]
[0195] A sintered body of an ion conductive solid containing an oxide of Example 30 was prepared by the same steps as in Example 1, except that the raw materials used in the above Examples were weighed in stoichiometric amounts so that b and c had the values shown in Table 1.
[0196] [Example 31]
[0197] A sintered body of an ion conductive solid containing an oxide of Example 31 was prepared by the same steps as in Example 1, except that the raw materials used in the above Examples were weighed in stoichiometric amounts so that b would have the value shown in Table 1.
[0198] [Example 32]
[0199] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass%), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Lu2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass%), Tb2O3 (manufactured by Shin-Etsu Chemical, purity 99.9 mass%), NiO (manufactured by Wako Pure Chemical Industries, Ltd., purity 99.0 mass%) and BaO (manufactured by Wako Pure Chemical Industries, Ltd., purity 90.0 mass%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and b became the values shown in Table 1. Except for this, the sintered body of the oxide-containing ion conductive solid of Example 32 was prepared by the same process as Example 1.
[0200] [Example 33]
[0201] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass%), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Lu2O3 (manufactured by Kojun Chemical Laboratory, purity 99.9 mass%), Tb2O3 (manufactured by Shin-Etsu Chemical Co., Ltd., purity 99.9 mass%), Ho2O3 (manufactured by Kojun Chemical Laboratory, purity 99.9 mass%) and BaO (manufactured by Wako Pure Chemical Industries, Ltd., purity 90.0 mass%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and b became the values shown in Table 1. Except for this, the sintered body of the oxide-containing ion conductive solid of Example 33 was prepared by the same process as Example 1.
[0202] [Example 34]
[0203] A sintered body of an ion conductive solid containing an oxide of Example 34 was prepared by the same steps as in Example 1, except that the raw materials used in the above Examples were weighed in stoichiometric amounts so that b, c, and d had the values shown in Table 1.
[0204] [Example 35]
[0205] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass%), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Lu2O3 (manufactured by Kojun Chemical Laboratory, purity 99.9 mass%), Er2O3 (manufactured by Shin-Etsu Chemical Co., Ltd., purity 95 mass%), Tm2O3 (manufactured by Kojun Chemical Laboratory, purity 99.9 mass%) and SrO (manufactured by Kojun Chemical Laboratory, purity 98 mass%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and b became the values recorded in Table 1. Except for this, the sintered body of the oxide-containing ion conductive solid of Example 35 was prepared by the same process as Example 1.
[0206] [Example 36]
[0207] A sintered body of an ion conductive solid containing an oxide of Example 36 was prepared by the same steps as in Example 1, except that the raw materials used in the above Examples were weighed in stoichiometric amounts so that b and c had the values shown in Table 1.
[0208] [Example 37]
[0209] A sintered body of an ion conductive solid containing an oxide of Example 37 was prepared by the same steps as in Example 1, except that the raw materials used in the above examples were weighed in stoichiometric amounts so that a, b, and c had the values shown in Table 1.
[0210] [Example 38]
[0211] A sintered body of an ion conductive solid containing an oxide of Example 38 was prepared by the same steps as in Example 1, except that the raw materials used in the above Examples were weighed in stoichiometric amounts so that b and d would have the values shown in Table 1.
[0212] [Example 39]
[0213] A sintered body of an ion conductive solid containing an oxide of Example 39 was prepared by the same steps as in Example 1, except that the raw materials used in the above examples were weighed in stoichiometric amounts so that b, c and d had the values shown in Table 1.
[0214] [Example 40]
[0215] A sintered body of an ion conductive solid containing an oxide of Example 40 was prepared by the same steps as in Example 1, except that the raw materials used in the above examples were weighed in stoichiometric amounts so that a, b, and c had the values shown in Table 1.
[0216] [Example 41]
[0217] A sintered body of an ion conductive solid containing an oxide of Example 41 was prepared by the same steps as in Example 1, except that the raw materials used in the above Examples were weighed in stoichiometric amounts so that b and d would have the values shown in Table 1.
[0218] [Example 42]
[0219] A sintered body of an ion conductive solid containing an oxide of Example 42 was prepared by the same steps as in Example 1, except that the raw materials used in the above Examples were weighed in stoichiometric amounts so that b and d would have the values shown in Table 1.
[0220] [Example 43]
[0221] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Lu2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass %) and Sc2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass %) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that b became the value recorded in Table 1. Except for this, a sintered body of an ion conductive solid containing oxide of Example 26 was prepared by the same process as Example 1.
[0222] [Example 44]
[0223] The raw materials used in the above examples were weighed in stoichiometric amounts so that a and b became the values shown in Table 1, and the disc speed during crushing was set to 300 rpm. Except for this, the sintered body of the ion conductive solid containing oxide of Example 44 was prepared by the same process as Example 1.
[0224] [Example 45]
[0225] The raw materials used in the above examples were weighed in stoichiometric amounts so that a and b became the values shown in Table 1, and the disc speed during crushing was set to 300 rpm. Except for this, the sintered body of the ion conductive solid containing oxide of Example 45 was prepared by the same process as Example 1.
[0226] [Example 46]
[0227] The raw materials used in the above examples were weighed in stoichiometric amounts so that a and b became the values shown in Table 1, and the disc speed during crushing was set to 300 rpm. Except for this, the sintered body of the ion conductive solid containing oxide of Example 46 was prepared by the same process as Example 1.
[0228] [Example 47]
[0229] The raw materials used in the above examples were weighed in stoichiometric amounts so that a and b became the values shown in Table 1, the disc speed during crushing was set to 150 rpm, and the crushing time was set to 60 minutes. Except for this, the sintered body of the ion-conductive solid containing oxide of Example 47 was prepared by the same process as in Example 1.
[0230] [Comparative Example 1]
[0231] A sintered body of an ion conductive solid containing oxide of Comparative Example 1 was prepared by the same steps as in Example 1, except that Lu 2 O 3 of the raw material in Example 1 was changed to Y 2 O 3 and each raw material was weighed in a stoichiometric amount so that d became the value described in Table 1.
[0232] [Comparative Example 2]
[0233] The sintered body of the ion conductive solid containing oxide of Comparative Example 2 was prepared by the same process as in Example 2, except that Lu2O3 of the raw material in Example 2 was changed to Y2O3 and each raw material was weighed in a stoichiometric amount so that c became the value described in Table 1.
[0234] [Comparative Example 3]
[0235] The sintered body of the ion conductive solid containing oxide of Comparative Example 3 was prepared by the same process as in Example 3, except that Lu2O3 of the raw material in Example 3 was changed to Y2O3 and each raw material was weighed in a stoichiometric amount so that c and d became the values shown in Table 1.
[0236] [Example 101]
[0237] ·One-shot firing process
[0238] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass%), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Ho2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass%), and Nb2O5 (manufactured by Mitsui Mining and Smelting, purity 99.9%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that d became the value recorded in Table 2, and mixed for 30 minutes at a disk speed of 300 rpm using a planetary mill P-7 manufactured by Fritsch. The planetary mill used was made of zirconium oxide. Ball and 45mL container.
[0239] After mixing, the mixed powder was cold uniaxially molded at 147 MPa using a 100 kN electric press device P3052-10 manufactured by NPASYSTEM, and then sintered in an air atmosphere at a heating temperature of 650° C. and a holding time of 720 minutes.
[0240] The obtained oxide-containing ion-conductive solid was pulverized for 180 minutes using a planetary mill P-7 manufactured by Fritsch Co., Ltd. at a disk rotation speed of 230 rpm to prepare a powder of the oxide-containing ion-conductive solid.
[0241] Secondary firing process
[0242] The powder of the ion conductive solid containing oxide obtained in the above manner was molded and secondary fired to prepare a sintered body of the ion conductive solid containing oxide of Example 101. The molding was performed by cold unidirectional molding of the powder at 147 MPa using a 100 kN electric press device P3052-10 manufactured by NPASYSTEM. The secondary firing was performed in an air atmosphere at a heating temperature of 650° C. and a holding time of 720 minutes.
[0243] [Example 102]
[0244] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Ho2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass %) and CeO2 (manufactured by Shin-Etsu Chemical Co., Ltd., purity 99.9%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that c became the value recorded in Table 2. Except for this, a sintered body of an ion-conductive solid containing oxide of Example 102 was prepared by the same process as Example 101.
[0245] [Example 103]
[0246] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Ho2O3 (manufactured by Kojun Chemical Laboratory, purity 99.9 mass %), ZrO2 (manufactured by Nippon Denko, purity 99.9%), CeO2 (manufactured by Shin-Etsu Chemical, purity 99.9%) and Nb2O5 (manufactured by Mitsui Mining and Smelting, purity 99.9%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that c and d became the values shown in Table 2. Except for this, a sintered body of an ion conductive solid containing oxide of Example 103 was prepared by the same process as Example 101.
[0247] [Example 104]
[0248] A sintered body of an ion conductive solid containing an oxide of Example 104 was prepared by the same steps as in Example 101, except that the respective raw materials used in the above Examples were weighed in stoichiometric amounts so as to obtain the values shown in Table 2.
[0249] [Example 105]
[0250] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Ho2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass %) and HfO2 (manufactured by New Metals, purity 99.9%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that c became the value recorded in Table 2. Except for this, a sintered body of an ion-conductive solid containing oxide of Example 105 was prepared by the same process as Example 101.
[0251] [Example 106]
[0252] A sintered body of an ion conductive solid containing an oxide of Example 106 was prepared by the same steps as in Example 101, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that c would have the value shown in Table 2.
[0253] [Example 107]
[0254] The sintered body of the ion conductive solid containing oxide of Example 107 was prepared by the same steps as in Example 101, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that c and d had the values shown in Table 2.
[0255] [Example 108]
[0256] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Ho2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass %), In2O3 (manufactured by Shinko Chemical Industry, purity 99 mass %) and SnO2 (manufactured by Mitsuwa Chemicals, purity 99.9%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that b and c became the values shown in Table 2. Except for this, a sintered body of an ion conductive solid containing oxide of Example 108 was prepared by the same process as Example 101.
[0257] [Example 109]
[0258] The sintered body of the ion conductive solid containing oxide of Example 109 was prepared by the same steps as in Example 101, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b and c had the values shown in Table 2.
[0259] [Example 110]
[0260] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Ho2O3 (manufactured by Kojun Chemical Laboratory, purity 99.9 mass %), Fe2O3 (manufactured by Wako Pure Chemical Industries, Ltd., purity 95.0 mass %) and TiO2 (manufactured by Toho Titanium Industry, purity 99%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that b and c became the values shown in Table 2. Except for this, a sintered body of an ion conductive solid containing oxide of Example 110 was prepared by the same process as Example 101.
[0261] [Example 111]
[0262] The sintered body of the ion conductive solid containing oxide of Example 111 was prepared by the same steps as in Example 101, except that the raw materials used in the above examples were weighed in stoichiometric amounts so that b and c had the values shown in Table 2.
[0263] [Example 112]
[0264] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Ho2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass %), MgO (manufactured by Ube Materials, purity 99.0 mass %) and CeO2 (manufactured by Shin-Etsu Chemical Co., Ltd., purity 99.9%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and c became the values shown in Table 2. Except for this, the sintered body of the oxide-containing ion conductive solid of Example 112 was prepared by the same process as Example 101.
[0265] [Example 113]
[0266] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass%), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Ho2O3 (manufactured by Kojun Chemical Laboratories, purity 99.9 mass%), La2O3 (manufactured by Wako Pure Chemical Industries, purity 99.9 mass%), MgO (manufactured by Ube Materials, purity 99.0 mass%) and CaO (manufactured by Kanto Chemical, purity 97.0 mass%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and b became the values shown in Table 2. Except for this, a sintered body of an ion conductive solid containing an oxide of Example 113 was prepared by the same process as Example 101.
[0267] [Example 114]
[0268] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Ho2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass %), Lu2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass %) and MnO (manufactured by Kanto Chemical, purity 80.0 mass %) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and b became the values shown in Table 2. Except for this, a sintered body of an ion conductive solid containing an oxide of Example 114 was prepared by the same process as Example 101.
[0269] [Example 115]
[0270] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Ho2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass %), Tb2O3 (manufactured by Shin-Etsu Chemical Co., Ltd., purity 99.9 mass %) and MnO (manufactured by Kanto Chemical, purity 80.0 mass %) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and b became the values shown in Table 2. Except for this, the sintered body of the oxide-containing ion conductive solid of Example 115 was prepared by the same process as Example 101.
[0271] [Example 116]
[0272] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Ho2O3 (manufactured by Kojun Chemical Laboratory, purity 99.9 mass %), Tm2O3 (manufactured by Kojun Chemical Laboratory, purity 99.9 mass %) and BaO (manufactured by Wako Pure Chemical Industries, Ltd., purity 90.0 mass %) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and b became the values shown in Table 2. Except for this, a sintered body of an ion conductive solid containing an oxide of Example 116 was prepared by the same process as Example 101.
[0273] [Example 117]
[0274] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Ho2O3 (manufactured by Kojun Chemical Laboratory, purity 99.9 mass %), SnO2 (manufactured by Mitsuwa Chemicals, purity 99.9%) and Nb2O5 (manufactured by Mitsui Mining and Smelting, purity 99.9%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that c and d became the values shown in Table 2. Except for this, a sintered body of an ion conductive solid containing oxide of Example 117 was prepared by the same process as Example 101.
[0275] [Example 118]
[0276] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass%), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Ho2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass%), In2O3 (manufactured by Shinko Chemical Industry, purity 99 mass%), Nb2O5 (manufactured by Mitsui Mining and Smelting, purity 99.9%) and Ta2O5 (manufactured by Kanto Chemical, purity 99 mass%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that b and d became the values shown in Table 2. Except for this, a sintered body of an ion conductive solid containing oxide of Example 118 was prepared by the same process as Example 101.
[0277] [Example 119]
[0278] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Ho2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass %) and Pr2O3 (manufactured by Shin-Etsu Chemical Co., Ltd., purity 99.9 mass %) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that b became the value recorded in Table 2. Except for this, a sintered body of an ion-conductive solid containing oxide of Example 119 was prepared by the same process as Example 101.
[0279] [Example 120]
[0280] The sintered body of the ion conductive solid containing oxide of Example 120 was prepared by the same steps as in Example 101, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b and d had the values shown in Table 2.
[0281] [Example 121]
[0282] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass%), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Ho2O3 (manufactured by Kojun Chemical Laboratories, purity 99.9 mass%), Sm2O3 (manufactured by Wako Pure Chemical Industries, Ltd., purity 99.9 mass%), HfO2 (manufactured by New Metals, purity 99.9%) and Ta2O5 (manufactured by Kanto Chemical, purity 99 mass%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that b, c and d became the values recorded in Table 2. Except for this, the sintered body of the oxide-containing ion conductive solid of Example 121 was prepared by the same process as Example 101.
[0283] [Example 122]
[0284] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Ho2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass %), Nd2O3 (manufactured by Shin-Etsu Chemical, purity 99.9 mass %), Sm2O3 (manufactured by Wako Pure Chemical Industries, Ltd., purity 99.9 mass %) and ZnO (manufactured by Wako Pure Chemical Industries, Ltd., purity 99 mass %) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and b became the values shown in Table 2. Except for this, the sintered body of the oxide-containing ion conductive solid of Example 122 was prepared by the same process as Example 101.
[0285] [Example 123]
[0286] The sintered body of the ion conductive solid containing oxide of Example 123 was prepared by the same steps as in Example 101, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b and c had the values shown in Table 2.
[0287] [Example 124]
[0288] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Ho2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass %) and Eu2O3 (manufactured by Shin-Etsu Chemical Co., Ltd., purity 95 mass %) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that b became the value recorded in Table 2. Except for this, a sintered body of an ion-conductive solid containing oxide of Example 124 was prepared by the same process as Example 101.
[0289] [Example 125]
[0290] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass%), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Ho2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass%), Eu2O3 (manufactured by Shin-Etsu Chemical Co., Ltd., purity 95 mass%) and NiO (manufactured by Wako Pure Chemical Industries, Ltd., purity 99.0 mass%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and b became the values shown in Table 2. Except for this, the sintered body of the oxide-containing ion conductive solid of Example 125 was prepared by the same process as Example 101.
[0291] [Example 126]
[0292] The sintered body of the ion conductive solid containing oxide of Example 126 was prepared by the same steps as in Example 101, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b and c had the values shown in Table 2.
[0293] [Example 127]
[0294] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass%), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Ho2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass%), Gd2O3 (manufactured by Shin-Etsu Chemical, purity 99.9 mass%), Dy2O3 (manufactured by Shin-Etsu Chemical, purity 95 mass%) and CaO (manufactured by Kanto Chemical, purity 99.0 mass%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and b became the values shown in Table 2. Except for this, the sintered body of the oxide-containing ion conductive solid of Example 127 was prepared by the same process as Example 101.
[0295] [Example 128]
[0296] The sintered body of the ion conductive solid containing oxide of Example 128 was prepared by the same steps as in Example 101, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b and c had the values shown in Table 2.
[0297] [Example 129]
[0298] The sintered body of the ion conductive solid containing oxide of Example 129 was prepared by the same steps as in Example 101, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b and c had the values shown in Table 2.
[0299] [Example 130]
[0300] The sintered body of the ion conductive solid containing oxide of Example 130 was prepared by the same steps as in Example 101, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b became the value shown in Table 2.
[0301] [Example 131]
[0302] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass%), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Ho2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass%), Tb2O3 (manufactured by Shin-Etsu Chemical, purity 99.9 mass%), NiO (manufactured by Wako Pure Chemical Industries, Ltd., purity 99.0 mass%) and BaO (manufactured by Wako Pure Chemical Industries, Ltd., purity 90.0 mass%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and b became the values shown in Table 2. Except for this, the sintered body of the oxide-containing ion conductive solid of Example 131 was prepared by the same process as Example 101.
[0303] [Example 132]
[0304] The sintered body of the ion conductive solid containing oxide of Example 132 was prepared by the same process as Example 101, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b, c and d had the values shown in Table 2.
[0305] [Example 133]
[0306] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass%), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Ho2O3 (manufactured by Kojun Chemical Laboratory, purity 99.9 mass%), Er2O3 (manufactured by Shin-Etsu Chemical Co., Ltd., purity 95 mass%), Tm2O3 (manufactured by Kojun Chemical Laboratory, purity 99.9 mass%) and SrO (manufactured by Kojun Chemical Laboratory, purity 98 mass%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and b became the values shown in Table 2. Except for this, the sintered body of the oxide-containing ion conductive solid of Example 133 was prepared by the same process as Example 101.
[0307] [Example 134]
[0308] The sintered body of the ion conductive solid containing oxide of Example 134 was prepared by the same steps as in Example 101, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b and c had the values shown in Table 2.
[0309] [Example 135]
[0310] The sintered body of the ion conductive solid containing oxide of Example 135 was prepared by the same process as Example 101, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that a, b and c had the values shown in Table 2.
[0311] [Example 136]
[0312] The sintered body of the ion conductive solid containing oxide of Example 136 was prepared by the same process as in Example 101, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b and d became the values shown in Table 2.
[0313] [Example 137]
[0314] The sintered body of the ion conductive solid containing oxide of Example 137 was prepared by the same process as Example 101, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b, c and d had the values shown in Table 2.
[0315] [Example 138]
[0316] The sintered body of the ion conductive solid containing oxide of Example 138 was prepared by the same process as Example 101, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that a, b and c had the values shown in Table 2.
[0317] [Example 139]
[0318] The sintered body of the ion conductive solid containing oxide of Example 139 was prepared by the same steps as in Example 101, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b and d had the values shown in Table 2.
[0319] [Example 140]
[0320] The sintered body of the ion conductive solid containing oxide of Example 140 was prepared by the same steps as in Example 101, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b and d had the values shown in Table 2.
[0321] [Example 141]
[0322] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Ho2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass %) and Sc2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass %) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that b became the value recorded in Table 2. Except for this, a sintered body of an ion conductive solid containing oxide of Example 141 was prepared by the same process as Example 101.
[0323] [Example 142]
[0324] The raw materials used in the above examples were weighed in stoichiometric amounts so that a and b became the values shown in Table 2, and the disc speed during crushing was set to 300 rpm. Except for this, the sintered body of the ion conductive solid containing oxide of Example 142 was prepared by the same process as Example 101.
[0325] [Example 143]
[0326] The raw materials used in the above examples were weighed in stoichiometric amounts so that a and b became the values shown in Table 2, and the disc speed during crushing was set to 300 rpm. Except for this, the sintered body of the ion-conductive solid containing oxide of Example 143 was prepared by the same process as Example 101.
[0327] [Example 144]
[0328] The raw materials used in the above examples were weighed in stoichiometric amounts so that a and b became the values shown in Table 2, and the disc speed during crushing was set to 300 rpm. Except for this, the sintered body of the ion-conductive solid containing oxide of Example 144 was prepared by the same process as Example 101.
[0329] [Example 201]
[0330] ·One-shot firing process
[0331] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass%), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Er2O3 (manufactured by Shin-Etsu Chemical, purity 95 mass%), and Nb2O5 (manufactured by Mitsui Mining & Smelting, purity 99.9%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that d became the value recorded in Table 3, and mixed for 30 minutes at a disk speed of 300 rpm using a planetary mill P-7 manufactured by Fritsch. The planetary mill used was made of zirconium oxide. Ball and 45mL container.
[0332] After mixing, the mixed powder was cold uniaxially molded at 147 MPa using a 100 kN electric press device P3052-10 manufactured by NPASYSTEM, and then sintered in an air atmosphere at a heating temperature of 650° C. and a holding time of 720 minutes.
[0333] The obtained oxide-containing ion conductive solid was pulverized for 180 minutes using a planetary mill P-7 manufactured by Fritsch Co., Ltd. at a disk rotation speed of 230 rpm to prepare a powder of the oxide-containing ion conductive solid.
[0334] Secondary firing process
[0335] The powder of the ion conductive solid containing oxide obtained in the above manner was molded and secondary fired to prepare a sintered body of the ion conductive solid containing oxide of Example 1. The molding was performed by cold unidirectional molding of the powder at 147 MPa using a 100 kN electric press device P3052-10 manufactured by NPASYSTEM. The secondary firing was performed in an air atmosphere at a heating temperature of 650° C. and a holding time of 720 minutes.
[0336] [Example 202]
[0337] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Er2O3 (manufactured by Shin-Etsu Chemical, purity 95 mass %) and CeO2 (manufactured by Shin-Etsu Chemical, purity 99.9%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that c became the value recorded in Table 3. Except for this, a sintered body of an ion-conductive solid containing oxide of Example 202 was prepared by the same process as Example 201.
[0338] [Example 203]
[0339] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Er2O3 (manufactured by Shin-Etsu Chemical, purity 95 mass %), ZrO2 (manufactured by Nippon Electric Industries, Ltd., purity 99.9%), CeO2 (manufactured by Shin-Etsu Chemical, purity 99.9%) and Nb2O5 (manufactured by Mitsui Mining and Smelting, purity 99.9%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that c and d became the values shown in Table 3. Except for this, a sintered body of an ion-conductive solid containing oxide of Example 203 was prepared by the same process as Example 201.
[0340] [Example 204]
[0341] A sintered body of an ion conductive solid containing an oxide of Example 204 was prepared by the same steps as in Example 201, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so as to obtain the values shown in Table 3.
[0342] [Example 205]
[0343] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Er2O3 (manufactured by Shin-Etsu Chemical, purity 95 mass %) and HfO2 (manufactured by New Metals, purity 99.9%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that c became the value recorded in Table 3. Except for this, a sintered body of an ion-conductive solid containing oxide of Example 205 was prepared by the same process as Example 201.
[0344] [Example 206]
[0345] The sintered body of the ion conductive solid containing oxide of Example 206 was prepared by the same steps as in Example 201, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that c became the value shown in Table 3.
[0346] [Example 207]
[0347] The sintered body of the ion conductive solid containing oxide of Example 207 was prepared by the same process as in Example 201, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that c and d had the values shown in Table 3.
[0348] [Example 208]
[0349] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Er2O3 (manufactured by Shin-Etsu Chemical Co., Ltd., purity 95 mass %), In2O3 (manufactured by Shinko Chemical Industry, purity 99 mass %) and SnO2 (manufactured by Mitsuwa Chemicals, purity 99.9%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that b and c became the values shown in Table 3. Except for this, a sintered body of an ion-conductive solid containing oxide of Example 208 was prepared by the same process as Example 201.
[0350] [Example 209]
[0351] The sintered body of the ion conductive solid containing oxide of Example 209 was prepared by the same process as in Example 201, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b and c had the values shown in Table 3.
[0352] [Example 210]
[0353] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Er2O3 (manufactured by Shin-Etsu Chemical, purity 95 mass %), Fe2O3 (manufactured by Wako Pure Chemical Industries, Ltd., purity 95.0 mass %) and TiO2 (manufactured by Toho Titanium, purity 99%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that b and c became the values shown in Table 3. Except for this, a sintered body of an ion conductive solid containing oxide of Example 210 was prepared by the same process as Example 201.
[0354] [Example 211]
[0355] The sintered body of the ion conductive solid containing oxide of Example 211 was prepared by the same process as Example 201, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b and c had the values shown in Table 3.
[0356] [Example 212]
[0357] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Er2O3 (manufactured by Shin-Etsu Chemical, purity 95 mass %), MgO (manufactured by Ube Materials, purity 99.0 mass %) and CeO2 (manufactured by Shin-Etsu Chemical, purity 99.9%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and c became the values shown in Table 3. Except for this, a sintered body of an ion conductive solid containing oxide of Example 212 was prepared by the same process as Example 201.
[0358] [Example 213]
[0359] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass%), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Er2O3 (manufactured by Shin-Etsu Chemical, purity 95 mass%), La2O3 (manufactured by Wako Pure Chemical Industries, purity 99.9 mass%), MgO (manufactured by Ube Materials, purity 99.0 mass%) and CaO (manufactured by Kanto Chemical, purity 97.0 mass%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and b became the values shown in Table 3. Except for this, a sintered body of an ion conductive solid containing an oxide of Example 213 was prepared by the same process as Example 201.
[0360] [Example 214]
[0361] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass%), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Er2O3 (manufactured by Shin-Etsu Chemical Co., Ltd., purity 95 mass%), Lu2O3 (manufactured by Kojun Chemical Laboratory, purity 99.9 mass%) and MnO (manufactured by Kanto Chemical, purity 80.0 mass%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and b had the values shown in Table 3. Except for this, a sintered body of an ion-conductive solid containing oxide of Example 214 was prepared by the same process as Example 201.
[0362] [Example 215]
[0363] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5 %), Er2O3 (manufactured by Shin-Etsu Chemical, purity 95 mass %), Tb2O3 (manufactured by Shin-Etsu Chemical, purity 99.9 mass %) and MnO (manufactured by Kanto Chemical, purity 80.0 mass %) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and b became the values shown in Table 3. Except for this, a sintered body of an ion conductive solid containing oxide of Example 215 was prepared by the same process as Example 201.
[0364] [Example 216]
[0365] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass%), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Er2O3 (manufactured by Shin-Etsu Chemical Co., Ltd., purity 95 mass%), Tm2O3 (manufactured by Kojun Chemical Laboratory, purity 99.9 mass%) and MnO (manufactured by Kanto Chemical, purity 80.0 mass%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and b had the values shown in Table 3. Except for this, a sintered body of an ion conductive solid containing oxide of Example 216 was prepared by the same process as Example 201.
[0366] [Example 217]
[0367] The sintered body of the ion conductive solid containing oxide of Example 217 was prepared by the same process as in Example 201, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that c and d became the values shown in Table 3.
[0368] [Example 218]
[0369] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass%), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Er2O3 (manufactured by Shin-Etsu Chemical, purity 95 mass%), In2O3 (manufactured by Shinko Chemical, purity 99 mass%), Nb2O5 (manufactured by Mitsui Mining and Smelting, purity 99.9%) and Ta2O5 (manufactured by Kanto Chemical, purity 99 mass%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that b and d became the values shown in Table 3. Except for this, a sintered body of an ion-conductive solid containing oxide of Example 218 was prepared by the same process as Example 201.
[0370] [Example 219]
[0371] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5% %), Er2O3 (manufactured by Shin-Etsu Chemical, purity 95 mass %) and Pr2O3 (manufactured by Shin-Etsu Chemical, purity 99.9 mass %) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that b became the value recorded in Table 3. Except for this, a sintered body of an ion-conductive solid containing oxide of Example 219 was prepared by the same process as Example 201.
[0372] [Example 220]
[0373] The sintered body of the ion conductive solid containing oxide of Example 220 was prepared by the same process as in Example 201, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b and d became the values shown in Table 3.
[0374] [Example 221]
[0375] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Er2O3 (manufactured by Shin-Etsu Chemical, purity 95 mass %), Sm2O3 (manufactured by Wako Pure Chemical Industries, purity 99.9 mass %), HfO2 (manufactured by New Metals, purity 99.9%) and Ta2O5 (manufactured by Kanto Chemical, purity 99 mass %) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that b, c and d became the values shown in Table 3. Except for this, the sintered body of the oxide-containing ion conductive solid of Example 221 was prepared by the same process as Example 201.
[0376] [Example 222]
[0377] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5 %), Er2O3 (manufactured by Shin-Etsu Chemical, purity 95 mass %), Nd2O3 (manufactured by Shin-Etsu Chemical, purity 99.9 mass %), Sm2O3 (manufactured by Wako Pure Chemical Industries, Ltd., purity 99.9 mass %) and ZnO (manufactured by Wako Pure Chemical Industries, Ltd., purity 99 mass %) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and b became the values shown in Table 3. Except for this, a sintered body of an ion conductive solid containing an oxide of Example 222 was prepared by the same process as Example 201.
[0378] [Example 223]
[0379] The sintered body of the ion conductive solid containing oxide of Example 223 was prepared by the same process as in Example 201, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b and c had the values shown in Table 3.
[0380] [Example 224]
[0381] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Er2O3 (manufactured by Shin-Etsu Chemical, purity 95 mass %) and Eu2O3 (manufactured by Shin-Etsu Chemical, purity 95 mass %) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that b became the value recorded in Table 3. Except for this, a sintered body of an ion-conductive solid containing oxide of Example 224 was prepared by the same process as Example 201.
[0382] [Example 225]
[0383] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass%), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Er2O3 (manufactured by Shin-Etsu Chemical, purity 95 mass%), Eu2O3 (manufactured by Shin-Etsu Chemical, purity 95 mass%) and NiO (manufactured by Wako Pure Chemical Industries, Ltd., purity 99.0 mass%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and b became the values shown in Table 3. Except for this, a sintered body of an ion conductive solid containing oxide of Example 225 was prepared by the same process as Example 201.
[0384] [Example 226]
[0385] The sintered body of the ion conductive solid containing oxide of Example 226 was prepared by the same process as in Example 201, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b and c became the values shown in Table 3.
[0386] [Example 227]
[0387] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass%), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Er2O3 (manufactured by Shin-Etsu Chemical, purity 95 mass%), Gd2O3 (manufactured by Shin-Etsu Chemical, purity 99.9 mass%), Dy2O3 (manufactured by Shin-Etsu Chemical, purity 95 mass%) and CaO (manufactured by Kanto Chemical, purity 99.0 mass%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and b became the values shown in Table 3. Except for this, the sintered body of the oxide-containing ion conductive solid of Example 227 was prepared by the same process as Example 201.
[0388] [Example 228]
[0389] The sintered body of the ion conductive solid containing oxide of Example 228 was prepared by the same process as in Example 201, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b and c became the values shown in Table 3.
[0390] [Example 229]
[0391] The sintered body of the ion conductive solid containing oxide of Example 229 was prepared by the same process as in Example 201, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b and c became the values shown in Table 3.
[0392] [Example 230]
[0393] The sintered body of the ion conductive solid containing oxide of Example 230 was prepared by the same process as in Example 201, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b became the value shown in Table 3.
[0394] [Example 231]
[0395] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass%), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Er2O3 (manufactured by Shin-Etsu Chemical, purity 95 mass%), Tb2O3 (manufactured by Shin-Etsu Chemical, purity 99.9 mass%), NiO (manufactured by Wako Pure Chemical Industries, Ltd., purity 99.0 mass%) and BaO (manufactured by Wako Pure Chemical Industries, Ltd., purity 90.0 mass%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and b became the values shown in Table 3. Except for this, a sintered body of an ion conductive solid containing an oxide of Example 231 was prepared by the same process as Example 201.
[0396] [Example 232]
[0397] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass%), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Er2O3 (manufactured by Shin-Etsu Chemical Co., Ltd., purity 95 mass%), Ho2O3 (manufactured by Kojun Chemical Laboratory, purity 99.9 mass%), Tb2O3 (manufactured by Shin-Etsu Chemical Laboratory, purity 99.9 mass%) and SrO (manufactured by Kojun Chemical Laboratory, purity 98 mass%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and b became the values shown in Table 3. Except for this, a sintered body of an ion conductive solid containing oxide of Example 232 was prepared by the same process as Example 201.
[0398] [Example 233]
[0399] The sintered body of the ion conductive solid containing oxide of Example 233 was prepared by the same process as in Example 201, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b, c and d became the values shown in Table 3.
[0400] [Example 234]
[0401] The sintered body of the ion conductive solid containing oxide of Example 234 was prepared by the same process as in Example 201, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b and d became the values shown in Table 3.
[0402] [Example 235]
[0403] The sintered body of the ion conductive solid containing oxide of Example 235 was prepared by the same process as in Example 201, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b, c and d became the values shown in Table 3.
[0404] [Example 236]
[0405] The sintered body of the ion conductive solid containing oxide of Example 236 was prepared by the same process as in Example 201, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that a, b and c became the values shown in Table 3.
[0406] [Example 237]
[0407] The sintered body of the ion conductive solid containing oxide of Example 237 was prepared by the same process as in Example 201, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b and d became the values shown in Table 3.
[0408] [Example 238]
[0409] The sintered body of the ion conductive solid containing oxide of Example 238 was prepared by the same process as in Example 201, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b and d became the values shown in Table 3.
[0410] [Example 239]
[0411] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5% %), Er2O3 (manufactured by Shin-Etsu Chemical Co., Ltd., purity 95 mass %) and Sc2O3 (manufactured by Kojun Chemical Laboratory, purity 99.9 mass %) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that b became the value recorded in Table 3. Except for this, a sintered body of an ion-conductive solid containing oxide of Example 239 was prepared by the same process as Example 201.
[0412] [Example 240]
[0413] The raw materials used in the above examples were weighed in stoichiometric amounts so that a and b became the values shown in Table 3, and the disc speed during crushing was set to 300 rpm. Except for this, the sintered body of the ion-conductive solid containing oxide of Example 240 was prepared by the same process as Example 201.
[0414] [Example 241]
[0415] The raw materials used in the above examples were weighed in stoichiometric amounts so that a and b became the values shown in Table 3, and the disc speed during crushing was set to 300 rpm. Except for this, the sintered body of the ion-conductive solid containing oxide of Example 241 was prepared by the same process as Example 201.
[0416] [Example 242]
[0417] The raw materials used in the above examples were weighed in stoichiometric amounts so that a and b became the values shown in Table 3, and the disc speed during crushing was set to 300 rpm. Except for this, the sintered body of the ion-conductive solid containing oxide of Example 242 was prepared by the same process as Example 201.
[0418] [Example 301]
[0419] ·One-shot firing process
[0420] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass%), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Tm2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass%), and Nb2O5 (manufactured by Mitsui Mining and Smelting, purity 99.9%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that d became the value described in Table 4, and mixed for 30 minutes at a disk speed of 300 rpm using a planetary mill P-7 manufactured by Fritsch. The planetary mill used was made of zirconium oxide. Ball and 45mL container.
[0421] After mixing, the mixed powder was cold uniaxially molded at 147 MPa using a 100 kN electric press device P3052-10 manufactured by NPASYSTEM, and then sintered in an air atmosphere at a heating temperature of 650° C. and a holding time of 720 minutes.
[0422] The obtained oxide-containing ion-conductive solid was pulverized for 180 minutes using a planetary mill P-7 manufactured by Fritsch Co., Ltd. at a disk rotation speed of 230 rpm to prepare a powder of the oxide-containing ion-conductive solid.
[0423] Secondary firing process
[0424] The powder of the ion conductive solid containing oxide obtained in the above manner was molded and secondary fired to prepare a sintered body of the ion conductive solid containing oxide of Example 301. The molding was performed by cold unidirectional molding of the powder at 147 MPa using a 100 kN electric press device P3052-10 manufactured by NPASYSTEM. The secondary firing was performed in an air atmosphere at a heating temperature of 650° C. and a holding time of 720 minutes.
[0425] [Example 302]
[0426] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Tm2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass %) and CeO2 (manufactured by Shin-Etsu Chemical Co., Ltd., purity 99.9%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that c became the value recorded in Table 4. Except for this, a sintered body of an ion-conductive solid containing oxide of Example 302 was prepared by the same process as Example 301.
[0427] [Example 303]
[0428] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Tm2O3 (manufactured by Kojun Chemical Laboratory, purity 99.9 mass %), ZrO2 (manufactured by Nippon Denko, purity 99.9%), CeO2 (manufactured by Shin-Etsu Chemical, purity 99.9%) and Nb2O5 (manufactured by Mitsui Mining and Smelting, purity 99.9%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that c and d became the values shown in Table 4. Except for this, a sintered body of an ion conductive solid containing oxide of Example 303 was prepared by the same process as Example 301.
[0429] [Example 304]
[0430] The sintered body of the ion conductive solid containing oxide of Example 304 was prepared by the same steps as in Example 301, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so as to obtain the values shown in Table 4.
[0431] [Example 305]
[0432] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Tm2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass %) and HfO2 (manufactured by New Metals, purity 99.9%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that c became the value recorded in Table 4. Except for this, a sintered body of an ion-conductive solid containing oxide of Example 305 was prepared by the same process as Example 301.
[0433] [Example 306]
[0434] The sintered body of the ion conductive solid containing oxide of Example 306 was prepared by the same steps as in Example 301, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that c became the value shown in Table 4.
[0435] [Example 307]
[0436] The sintered body of the ion conductive solid containing oxide of Example 307 was prepared by the same process as in Example 301, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that c and d had the values shown in Table 4.
[0437] [Example 308]
[0438] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Tm2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass %), In2O3 (manufactured by Shinko Chemical Industry, purity 99 mass %) and SnO2 (manufactured by Mitsuwa Chemicals, purity 99.9%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that b and c became the values shown in Table 4. Except for this, a sintered body of an ion conductive solid containing oxide of Example 308 was prepared by the same process as Example 301.
[0439] [Example 309]
[0440] The sintered body of the ion conductive solid containing oxide of Example 309 was prepared by the same process as in Example 301, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b and c had the values shown in Table 4.
[0441] [Example 310]
[0442] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Tm2O3 (manufactured by Kojun Chemical Laboratory, purity 99.9 mass %), Fe2O3 (manufactured by Wako Pure Chemical Industries, Ltd., purity 95.0 mass %) and TiO2 (manufactured by Toho Titanium Industry, purity 99%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that b and c became the values shown in Table 4. Except for this, a sintered body of an ion conductive solid containing oxide of Example 310 was prepared by the same process as Example 301.
[0443] [Example 311]
[0444] The sintered body of the ion conductive solid containing oxide of Example 311 was prepared by the same process as Example 301, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b and c had the values shown in Table 4.
[0445] [Example 312]
[0446] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Tm2O3 (manufactured by Kojun Chemical Laboratory, purity 99.9 mass %), MgO (manufactured by Ube Materials, purity 99.0 mass %) and CeO2 (manufactured by Shin-Etsu Chemical Co., Ltd., purity 99.9%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and c became the values shown in Table 4. Except for this, a sintered body of an ion conductive solid containing oxide of Example 312 was prepared by the same process as Example 301.
[0447] [Example 313]
[0448] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass%), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Tm2O3 (manufactured by Kojun Chemical Laboratories, purity 99.9 mass%), La2O3 (manufactured by Wako Pure Chemical Industries, purity 99.9 mass%), MgO (manufactured by Ube Materials, purity 99.0 mass%) and CaO (manufactured by Kanto Chemical, purity 97.0 mass%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and b became the values shown in Table 4. Except for this, a sintered body of an ion conductive solid containing an oxide of Example 313 was prepared by the same process as Example 301.
[0449] [Example 314]
[0450] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Tm2O3 (manufactured by Kojun Chemical Laboratory, purity 99.9 mass %), Lu2O3 (manufactured by Kojun Chemical Laboratory, purity 99.9 mass %) and MnO (manufactured by Kanto Chemical, purity 80.0 mass %) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and b became the values shown in Table 4. Except for this, a sintered body of an ion conductive solid containing oxide of Example 314 was prepared by the same process as Example 301.
[0451] [Example 315]
[0452] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Tm2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass %), Tb2O3 (manufactured by Shin-Etsu Chemical Co., Ltd., purity 99.9 mass %) and MnO (manufactured by Kanto Chemical, purity 80.0 mass %) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and b had the values shown in Table 4. Except for this, a sintered body of an ion conductive solid containing oxide of Example 315 was prepared by the same process as Example 301.
[0453] [Example 316]
[0454] The sintered body of the ion conductive solid containing oxide of Example 316 was prepared by the same process as in Example 301, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that c and d became the values shown in Table 4.
[0455] [Example 317]
[0456] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Tm2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass %), In2O3 (manufactured by Shinko Chemical Industry, purity 99 mass %), Nb2O5 (manufactured by Mitsui Mining and Smelting, purity 99.9%) and Ta2O5 (manufactured by Kanto Chemical, purity 99 mass %) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that b and d became the values shown in Table 4. Except for this, a sintered body of an ion conductive solid containing oxide of Example 317 was prepared by the same process as Example 301.
[0457] [Example 318]
[0458] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Tm2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass %) and Pr2O3 (manufactured by Shin-Etsu Chemical Co., Ltd., purity 99.9 mass %) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that b became the value recorded in Table 4. Except for this, a sintered body of an ion-conductive solid containing oxide of Example 318 was prepared by the same process as Example 301.
[0459] [Example 319]
[0460] The sintered body of the ion conductive solid containing oxide of Example 319 was prepared by the same process as in Example 301, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b and d became the values shown in Table 4.
[0461] [Example 320]
[0462] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Tm2O3 (manufactured by Kojun Chemical Laboratories, purity 99.9 mass %), Sm2O3 (manufactured by Wako Pure Chemical Industries, Ltd., purity 99.9 mass %), HfO2 (manufactured by New Metals, purity 99.9%) and Ta2O5 (manufactured by Kanto Chemical, purity 99 mass %) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that b, c and d became the values shown in Table 4. Except for this, a sintered body of an ion conductive solid containing oxide of Example 320 was prepared by the same process as Example 301.
[0463] [Example 321]
[0464] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Tm2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass %), Nd2O3 (manufactured by Shin-Etsu Chemical, purity 99.9 mass %), Sm2O3 (manufactured by Wako Pure Chemical Industries, Ltd., purity 99.9 mass %) and ZnO (manufactured by Wako Pure Chemical Industries, Ltd., purity 99 mass %) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and b became the values shown in Table 4. Except for this, a sintered body of an ion conductive solid containing an oxide of Example 321 was prepared by the same process as Example 301.
[0465] [Example 322]
[0466] The sintered body of the ion conductive solid containing oxide of Example 322 was prepared by the same process as in Example 301, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b and c had the values shown in Table 4.
[0467] [Example 323]
[0468] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Tm2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass %) and Eu2O3 (manufactured by Shin-Etsu Chemical Co., Ltd., purity 95 mass %) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that b became the value recorded in Table 4. Except for this, a sintered body of an ion-conductive solid containing oxide of Example 323 was prepared by the same process as Example 301.
[0469] [Example 324]
[0470] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass%), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Tm2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass%), Eu2O3 (manufactured by Shin-Etsu Chemical Co., Ltd., purity 95 mass%) and NiO (manufactured by Wako Pure Chemical Industries, Ltd., purity 99.0 mass%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and b became the values shown in Table 4. Except for this, a sintered body of an ion conductive solid containing oxide of Example 324 was prepared by the same process as Example 301.
[0471] [Example 325]
[0472] The sintered body of the ion conductive solid containing oxide of Example 325 was prepared by the same process as in Example 301, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b and c became the values shown in Table 4.
[0473] [Example 326]
[0474] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass%), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Tm2O3 (manufactured by Kojun Chemical Laboratory, purity 99.9 mass%), Gd2O3 (manufactured by Shin-Etsu Chemical, purity 99.9 mass%), Dy2O3 (manufactured by Shin-Etsu Chemical, purity 95 mass%) and CaO (manufactured by Kanto Chemical, purity 99.0 mass%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and b became the values shown in Table 4. Except for this, a sintered body of an ion conductive solid containing oxide of Example 326 was prepared by the same process as Example 301.
[0475] [Example 327]
[0476] The sintered body of the ion conductive solid containing oxide of Example 327 was prepared by the same process as in Example 301, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b and c became the values shown in Table 4.
[0477] [Example 328]
[0478] The sintered body of the ion conductive solid containing oxide of Example 328 was prepared by the same process as in Example 301, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b and c became the values shown in Table 4.
[0479] [Example 329]
[0480] The sintered body of the ion conductive solid containing oxide of Example 329 was prepared by the same process as in Example 301, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b became the value shown in Table 4.
[0481] [Example 330]
[0482] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass%), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Tm2O3 (manufactured by Kojun Chemical Laboratory, purity 99.9 mass%), Tb2O3 (manufactured by Shin-Etsu Chemical Co., Ltd., purity 99.9 mass%), NiO (manufactured by Wako Pure Chemical Industries, Ltd., purity 99.0 mass%) and BaO (manufactured by Wako Pure Chemical Industries, Ltd., purity 90.0 mass%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and b became the values shown in Table 4. Except for this, a sintered body of an ion conductive solid containing an oxide of Example 330 was prepared by the same process as Example 301.
[0483] [Example 331]
[0484] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass%), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Tm2O3 (manufactured by Kojun Chemical Laboratory, purity 99.9 mass%), Tb2O3 (manufactured by Shin-Etsu Chemical Co., Ltd., purity 99.9 mass%), Ho2O3 (manufactured by Kojun Chemical Laboratory, purity 99.9 mass%) and BaO (manufactured by Wako Pure Chemical Industries, Ltd., purity 90.0 mass%) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and b became the values shown in Table 4. Except for this, a sintered body of an ion conductive solid containing an oxide of Example 331 was prepared by the same process as Example 301.
[0485] [Example 332]
[0486] The sintered body of the ion conductive solid containing oxide of Example 332 was prepared by the same process as in Example 301, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b, c and d became the values shown in Table 4.
[0487] [Example 333]
[0488] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Tm2O3 (manufactured by Kojun Chemical Laboratory, purity 99.9 mass %), Ho2O3 (manufactured by Kojun Chemical Laboratory, purity 99.9 mass %), Er2O3 (manufactured by Shin-Etsu Chemical Industry, purity 95 mass %) and SrO (manufactured by Kojun Chemical Laboratory, purity 98 mass %) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that a and b became the values shown in Table 4. Except for this, a sintered body of an ion conductive solid containing oxide of Example 333 was prepared by the same process as Example 301.
[0489] [Example 334]
[0490] The sintered body of the ion conductive solid containing oxide of Example 334 was prepared by the same process as in Example 301, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b and c became the values shown in Table 4.
[0491] [Example 335]
[0492] The sintered body of the ion conductive solid containing oxide of Example 335 was prepared by the same process as Example 301, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that a, b and c had the values shown in Table 4.
[0493] [Example 336]
[0494] The sintered body of the ion conductive solid containing oxide of Example 336 was prepared by the same process as in Example 301, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that a, b and c became the values shown in Table 4.
[0495] [Example 337]
[0496] The sintered body of the ion conductive solid containing oxide of Example 337 was prepared by the same process as in Example 301, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b and d became the values shown in Table 4.
[0497] [Example 338]
[0498] The sintered body of the ion conductive solid containing oxide of Example 338 was prepared by the same process as in Example 301, except that the respective raw materials used in the above examples were weighed in stoichiometric amounts so that b and d became the values shown in Table 4.
[0499] [Example 339]
[0500] Li2CO3 (manufactured by Nacalai Tesque, purity 99.0 mass %), H3BO3 (manufactured by Kanto Chemical, purity 99.5%), Tm2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass %) and Sc2O3 (manufactured by Kojun Chemical Research Institute, purity 99.9 mass %) were used as raw materials, and each raw material was weighed in a stoichiometric amount so that b became the value recorded in Table 4. Except for this, a sintered body of an ion-conductive solid containing oxide of Example 339 was prepared by the same process as Example 301.
[0501] [Example 340]
[0502] The raw materials used in the above examples were weighed in stoichiometric amounts so that a and b became the values shown in Table 4, and the disc speed during crushing was set to 300 rpm. Except for this, the sintered body of the ion-conductive solid containing oxide of Example 340 was prepared by the same process as Example 301.
[0503] [Example 341]
[0504] The raw materials used in the above examples were weighed in stoichiometric amounts so that a and b became the values shown in Table 4, and the disc speed during crushing was set to 300 rpm. Except for this, the sintered body of the ion-conductive solid containing oxide of Example 341 was prepared by the same process as Example 301.
[0505] [Example 342]
[0506] The raw materials used in the above examples were weighed in stoichiometric amounts so that a and b became the values shown in Table 4, and the disc speed during crushing was set to 300 rpm. Except for this, the sintered body of the ion-conductive solid containing oxide of Example 342 was prepared by the same process as Example 301.
[0507] [Comparative Example 4]
[0508] The raw material Tm2O3 in Example 4 was changed to Sc2O3 (Sc 3+ Ionic radius: ), when prepared by the same process as in Example 4, the same crystal structure as in Example 4 could not be obtained. The impedance of the obtained sintered body was measured by the method described later, but the resistance of the sintered body could not be measured, and the ion conductivity could not be obtained as a numerical value.
[0509] [Comparative Example 5]
[0510] The raw material Tm2O3 in Example 4 was changed to Fe2O3 (Fe 3+ Ionic radius: ), when prepared by the same process as in Example 4, the same crystal structure as in Example 4 could not be obtained. The impedance of the obtained sintered body was measured by the method described later, but the resistance of the sintered body could not be measured, and the ion conductivity could not be obtained as a numerical value.
[0511] [Comparative Example 6]
[0512] The raw material Tm2O3 in Example 4 was changed to La2O3 (La 3+ Ionic radius: ), when prepared by the same process as in Example 4, the same crystal structure as in Example 4 could not be obtained. The impedance of the obtained sintered body was measured by the method described later, but the resistance of the sintered body could not be measured, and the ion conductivity could not be obtained as a numerical value.
[0513] Composition analysis was performed by the above method on the sintered bodies of the ion conductive solid containing oxides of Examples 1 to 47, 101 to 144, 201 to 242, and 301 to 342. In addition, the volume average particle size of the powder of the ion conductive solid obtained by Examples 1 to 47, 101 to 144, 201 to 242, and 301 to 342 and Comparative Examples 1 to 3 and the ion conductivity of the sintered bodies of the ion conductive solid were measured by the following method.
[0514] The methods for measuring the ion conductivity and the volume average particle size are described below. In addition, the obtained evaluation results are shown in Tables 1, 2, 3 and 4.
[0515] Determination of ionic conductivity
[0516] In the flat plate-shaped sintered body of the ion conductive solid containing oxide obtained by secondary sintering, two parallel and large-area surfaces are polished with sandpaper. The size of the flat plate-shaped sintered body of the ion conductive solid containing oxide can be, for example, 0.9 cm × 0.9 cm × 0.05 cm, but is not limited to this. The polishing starts with polishing with #500 for 15 minutes to 30 minutes, then polishing with #1000 for 10 minutes to 20 minutes, and finally polishing with #2000 for 5 minutes to 10 minutes. If there are no visually conspicuous bumps or scratches on the polished surface, it is completed.
[0517] After grinding, a gold film was formed on the ground surface of the sintered body of the oxide-containing ion conductive solid using a sputtering device SC-701MkII ADVANCE manufactured by Sanyu Electronics. The film forming conditions were that the process gas was Ar, the vacuum was 2Pa to 5Pa, and the film forming time was 5 minutes. The sample was used as the measurement sample. After the film was formed, the AC impedance of the measurement sample was measured.
[0518] The impedance measurement used an impedance / gain phase analyzer SI1260 and a dielectric interface system 1296 (both manufactured by SOLARTRON) under the following measurement conditions: a temperature of 27° C., an amplitude of 20 mV, and a frequency of 0.1 Hz to 1 MHz.
[0519] The resistance of the sintered body of the ion-conducting solid containing oxide was calculated using the Nyquist curve obtained by impedance measurement and the AC analysis software manufactured by Scribner. An equivalent circuit corresponding to the measured sample was set in ZVIEW, and the equivalent circuit and the Nyquist curve were fitted and analyzed to calculate the resistance of the sintered body of the ion-conducting solid containing oxide. The ion conductivity was calculated by the following formula using the calculated resistance and the thickness and electrode area of the sintered body of the ion-conducting solid containing oxide.
[0520] Ion conductivity (S / cm) = thickness of sintered body of ion conductive solid containing oxide (cm) / (resistance of sintered body of ion conductive solid containing oxide (Ω) × electrode area (cm) 2 ))
[0521] The ion conductivity (S / cm) of the sintered body of the ion conductive solid is preferably 8.00×10 -9 More preferably, 1.00×10 -8 More preferably, 1.00×10 -7 More preferably, 1.00×10 -6 More than 1.00×10 -5 The higher the conductivity, the better. The upper limit is not particularly limited, but for example, 1.00×10 -2 Below, 1.00×10 -3 Below, 1.00×10 -4 the following.
[0522] ·Evaluation of volume average particle size
[0523] The particle size distribution of the powder of the ion-conductive solid containing oxide obtained by the ball mill treatment (P-7 planetary mill manufactured by Fritsch Co.) after the primary firing was measured using the laser diffraction / scattering particle size distribution measuring device LA-960V2 manufactured by Horiba Seika. The refractive index was 1.8, and ethanol was used as the measuring solvent. The concentration of the sample was adjusted so that the transmittance was 90 to 70%. The volume average particle size was calculated based on the obtained frequency distribution.
[0524] ·result
[0525] Tables 1, 2, 3 and 4 show the stoichiometric amounts of the raw materials (general formula Li 6+a-c-2d X 1-a-b-c-d M1 a M2 bM3 c M4 d The values of a, b, c and d in B3O9), volume average particle size and ionic conductivity.
[0526] The results of the above composition analysis confirmed that the sintered bodies of the ion conductive solid containing oxide of Examples 1 to 47, 101 to 144, 201 to 242, and 301 to 342 and Comparative Examples 1 to 3 all had compositions as described in the stoichiometric amounts of the raw materials in Tables 1, 2, 3, and 4. In addition, the sintered bodies of the ion conductive solid containing oxide of Examples 1 to 47, 101 to 144, 201 to 242, and 301 to 342 were ion conductive solids that showed high ion conductivity even when sintered at a temperature lower than 700°C.
[0527] [Table 1]
[0528] Table 1
[0529]
[0530] In the table, Comparative Examples 1 to 3 are composed of the general formula Li 6+a-c-2d Y 1-a-b-c-d M1 a M2 b M3 c M4 d Oxide represented by B3O9.
[0531] [Table 2]
[0532] Table 2
[0533]
[0534] In the table, Comparative Examples 1 to 3 are composed of the general formula Li 6+a-c-2d Y 1-a-b-c-d M1 a M2 b M3 c M4 d Oxide represented by B3O9.
[0535] [Table 3]
[0536] Table 3
[0537]
[0538] In the table, Comparative Examples 1 to 3 are composed of the general formula Li 6+a-c-2d Y 1-a-b-c-d M1 a M2 b M3 c M4 d Oxide represented by B3O9.
[0539] [Table 4]
[0540] Table 4
[0541]
[0542] In the table, Comparative Examples 1 to 3 are composed of the general formula Li 6+a-c-2d Y 1-a-b-c-d M1 a M2 b M3 c M4 d Oxide represented by B3O9.
[0543] Tables 1, 2, 3 and 4 show that the ion conductivity of the ion conductive solids prepared by Examples 1, 101, 201 and 301 is improved compared with Comparative Example 1, and higher ion conductivity can be obtained by replacing Y with at least one selected from the group consisting of Lu, Ho, Er and Tm. It can be seen that higher ion conductivity can be obtained by replacing Y in the composition disclosed in the prior art with at least one selected from the group consisting of Lu, Ho, Er and Tm which is a metal element with a small ion radius.
[0544] Table 1 shows that the ion conductivity of the ion conductive solids prepared by Examples 1 to 3 is improved compared with Comparative Examples 1 to 3, and higher ion conductivity can be obtained by replacing Y with Lu. It can be seen that higher ion conductivity can be obtained by replacing Y in the composition disclosed in the prior art with Lu having a small ion radius.
[0545] In addition, the ion conductivity of the ion conductive solids prepared by Examples 44 to 46 was improved compared with Examples 16, 26 and 32. Since the compositions and substitution elements disclosed in the prior art are different, the density after sintering may be affected by the difference in melting points, and the appropriate range of particle size may be different.
[0546] Table 2 shows that the ion conductivity of the ion conductive solids prepared by Examples 101 to 103 is improved compared to Comparative Examples 1 to 3, and higher ion conductivity can be obtained by replacing Y with Ho. It can be seen that higher ion conductivity can be obtained by replacing Y in the composition disclosed in the prior art with Ho having a small ion radius.
[0547] In addition, the ion conductivity of the ion conductive solid prepared by Examples 142 to 144 was improved compared with Examples 115, 125, and 131. Since the compositions and substitution elements disclosed in the prior art are different, the density after sintering may be affected by the difference in melting points, and the appropriate range of particle size may be different.
[0548] Table 3 shows that the ion conductivity of the ion conductive solids prepared by Examples 201 to 203 is improved compared to Comparative Examples 1 to 3, and higher ion conductivity can be obtained by replacing Y with Er. It can be seen that higher ion conductivity can be obtained by replacing Y in the composition disclosed in the prior art with Er having a small ion radius.
[0549] In addition, the ion conductivity of the ion conductive solid prepared by Examples 240 to 242 was improved compared with that of Examples 215, 225, and 231. Since the compositions and substitution elements disclosed in the prior art are different, the density after sintering may be affected by the difference in melting points, and the appropriate range of particle size may be different.
[0550] Table 4 shows that the ion conductivity of the ion conductive solids prepared by Examples 301 to 303 is improved compared to Comparative Examples 1 to 3, and higher ion conductivity can be obtained by replacing Y with Tm. It can be seen that higher ion conductivity can be obtained by replacing Y in the composition disclosed in the prior art with Tm having a small ion radius.
[0551] In addition, the ion conductivity of the ion conductive solid prepared by Examples 340 to 342 was improved compared with Examples 315, 324, and 330. Since the composition and substitution elements disclosed in the prior art are different, the density after sintering may be affected by the difference in melting point, and the appropriate range of particle size may be different.
Claims
1. An ion-conductive solid, characterized in that Containing the general formula Li 6+a-c-2d X 1-a-b-c-d M1 a M2 b M3 c M4 d Oxide represented by B3O9, In the formula, X is at least one metal element selected from the group consisting of Lu, Ho, Er and Tm, M1 is at least one metal element selected from the group consisting of Mg, Mn, Zn, Ni, Ca, Sr and Ba, M2 is at least one metal element selected from the group consisting of La, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Lu, In, Fe and Sc, M3 is at least one metal element selected from the group consisting of Zr, Ce, Hf, Sn and Ti, M4 is at least one metal element selected from the group consisting of Nb and Ta, a is a real number satisfying 0.000≤a≤0.800, b is a real number satisfying 0.000≤b≤0.900, c is a real number satisfying 0.000≤c≤0.800, d is a real number satisfying 0.000≤d≤0.800, a, b, c, d are real numbers satisfying 0.000≤a+b+c+d<1.000, except when X and M2 are the same metal element.
2. The ion-conductive solid according to claim 1, characterized in that The 1-abcd is 0.300≤1-abcd.
3. The ion-conductive solid according to claim 1 or 2, characterized in that The 1-abcd is 0.500≤1-abcd.
4. The ion-conductive solid according to any one of claims 1 to 3, characterized in that The a is 0.000≤a≤0.
400.
5. The ion-conductive solid according to any one of claims 1 to 4, characterized in that The b is 0.000≤b≤0.
500.
6. The ion-conductive solid according to any one of claims 1 to 5, characterized in that The c is 0.000≤c≤0.
400.
7. The ion-conductive solid according to any one of claims 1 to 6, characterized in that The d is 0.000≤d≤0.
400.
8. The ion-conductive solid according to any one of claims 1 to 7, characterized in that The volume average particle size is 0.1 μm or more and 28.0 μm or less.
9. An all-solid-state battery, comprising at least a positive electrode, a negative electrode and an electrolyte, in, At least one selected from the group consisting of the positive electrode, the negative electrode, and the electrolyte contains the ion-conductive solid according to any one of claims 1 to 8.
10. The all-solid-state battery according to claim 9, characterized in that: At least the electrolyte contains the ion-conductive solid.